CONSTITUTION – THE BASIS OF THE LEGAL SYSTEM OF THE STATE (Scientific journal of the Fergana State University, 2023)
This article reveals the meaning of the concept of “constitution”, describes the issues of the foundations of the legal system of the state - Constitution of the Republic of Uzbekistan, its purpose, essence, content, features, legal guarantees of citizens, the role and significance of the Basic Law of our country, and also discusses the main ideas and issues of state ideology; as well as the types and order of relations between a citizen of the country and the state.